Penetrasi Bank Digital dan Inklusi Keuangan Rumah Tangga Perdesaan di Nusa Tenggara Barat: Pendekatan Structural Equation Modeling - Mahadewi, Ni Luh Ayu Puspita; Syahputra, Muhammad Rafiq Fathurrahman (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study examines the impact of digital banking penetration on rural household financial inclusion in West Nusa Tenggara using a Partial Least Squares Structural Equation Modeling approach. The research is motivated by limited access to formal financial services in rural areas and the rapid expansion of digital banking services over the past decade. The proposed model investigates the relationships among digital infrastructure, digital literacy, trust, digital banking penetration, and financial inclusion. Data were collected from 352 rural households selected through multistage random sampling. The analysis involved measurement and structural model assessments to ensure validity, reliability, and the significance of relationships among constructs. The findings reveal that digital banking penetration has a positive and significant effect on rural household financial inclusion. Digital infrastructure and digital literacy significantly enhance digital banking penetration, while trust strengthens the adoption and sustained use of digital financial services. The R square value of 0.63 indicates strong explanatory power of the model in explaining variations in financial inclusion. Mediation analysis confirms that digital literacy mediates the relationship between digital banking penetration and financial inclusion. The study concludes that improving rural financial inclusion requires more than expanding digital banking services. It demands adequate digital infrastructure, strong digital literacy, and high levels of trust in digital financial systems. Policy implications highlight the need for integrated strategies that combine infrastructure development, digital literacy programs, and consumer protection frameworks to foster sustainable financial inclusion in rural areas.